Strategi Pemerintah Dalam Penerapan Aplikasi Identitas Kependudukan Digital (IKD) Oleh Dinas Kependudukan dan Pencatatan Sipil Kabupaten Cirebon - Viona Azzahra; Rudiana, Rudiana (Universitas Ekasakti, 2024)
This research is entitled Government Strategy in Implementing the Digital Population Identity (IKD) Application by the Cirebon Regency Population and Civil Registration Service in 2022. This research is motivated by the ineffectiveness of the efforts of the Cirebon Regency government, especially the Population and Civil Registration Service, in the outreach carried out to the community as it should be. completed in an appropriate manner regarding the implementation of the Digital Population Identity Application which, if implemented properly, will make it easier for the public to apply for services related to population administration. This research aims to analyze and describe the Government's Strategy in Implementing the Digital Population Identity (IKD) Application by the Cirebon Regency Population and Civil Registration Service in implementing the Digital Population Identity Application (IKD). The research method used is a descriptive method with a qualitative approach. The data obtained comes from research results through literature studies and field studies through observation, interviews and documentation. The objective component is related to the strategic objectives of the Cirebon Regency government in terms of implementing the Digital Population Identity Application. Environmental components, internal and external environmental conditions that contain potential threats in the Cirebon Regency government strategy in implementing the Digital Population Identity Application. Direction component, in its implementation there are directions given by the Cirebon Regency Population and Civil Registration Service to related parties. The action component is carried out by implementing the Digitak Population Identity Application through several programs which will have an impact on improving public services in Cirebon Regency. The learning component has advantages and disadvantages in implementation, so an evaluation is carried out. Based on the research results, it can be concluded that based on the explanation and analysis of the Government's Strategy in Implementing the Digital Population Identity (IKD) Application by the Cirebon Regency Population and Civil Registration Service, it has not been implemented effectively and is still far from optimal.